ANALISIS DISTRIBUSI REKAHAN DAN STILOLYTE MENGGUNAKAN DATA SINGKAPAN DAN DATA SUMUR PADA BATUGAMPING FORMASI RAJAMANDALA DI AREA CIKAMUNING, PADALARANG, JAWA BARAT-INDONESIA - HERLAMBANG , ADHIPA
Naturally fractured reservoir is one of proven as productive reservoir in numerous oilfields. Limestone is one of the lithology as a naturally fractured reservoir. However, there are still many problems that have not been well understood, especially the correlation between fractures and stylolite distribution with facies and diagenetics. Rajamandala carbonate complex cropped out in Padalarang area, West Java, has been subject for detail studied by various researcher.